A REVIEW OF HELMINTH SPECIES IN REPTILES OF UZBEKISTAN: FAMILIES TESTUDINIDAE, GEKKONIDAE, AGAMIDAE, ANGUIDAE, LACERTIDAE, AND SCINCIDAE - E.F. Ikromov, E.F. Ikromov; E.E. Ikromov, E.E. Ikromov; I.K. Rustamov, I.K. Rustamov (Actual problems and prospects of the study of the fauna, 2024)
This study provides a comprehensive overview of the helminth species associated with reptiles belonging to the families Testudinidae, Gekkonidae, Agamidae, Anguidae, Lacertidae, and Scincidae in Uzbekistan. By examining various reptilian hosts, the research identifies and catalogs the diversity of helminths in these families. The findings contribute to the understanding of host-parasite dynamics and have implications for the conservation and health management of reptile populations in Uzbekistan. Additionally, this work underscores the importance of further research into the ecological interactions between reptiles and their parasitic fauna.